Coercion and provocation - Dafoe, A; Hatz, S; Zhang, B (SAGE Publications, 2020)
Threats and force, by increasing expected costs, should reduce the target’s resolve. However, they often seem to increase resolve. We label this phenomenon provocation. We review instances of apparent provocation in interstate relations and offer a theory based on the logic of reputation and honor. We also consider alternative explanations: confounding or misimputation of resolve, revelation of information, character, or capabilities, or generalized sunk cost reasoning. Using survey experiments we systematically evaluate whether provocation exists and what may account for it. We employ design-based causal inference techniques — a hypothetical natural experiment, a placebo treatment, and ruling out mediators — to evaluate our key hypotheses. We find strong evidence of provocation, and suggestive evidence that it arises from considerations of honor, vengeance, and reputation. Our experimental design minimizes the risk that this result arises from our alternative explanations.